Headache in Pregnancy: A Nuisance or a New Sense? - Archana Dixit; Manish Bhardwaj; Bhavna Sharma (Obstetrics and Gynecology International)
Headache is a very commonly encountered symptom in pregnancy and is usually due to primary headache disorders which are benign in nature. It can however be quite debilitating for some women who may need therapeutic treatment of which there are several options safe to use in pregnancy. It is equally important though to recognise that headache may be a sign of serious underlying pathology. This paper aims to provide a clinically useful guidance for differentiation between primary and secondary headaches in pregnancy. The primary headache disorders and their management in pregnancy are explored in depth with brief overviews of the causes for secondary headaches and their further investigation and management.